Kebangkitan Seorang Nabi: Kajian Pandangan di Kalangan Kristen dan Tokoh Islam Mengenai Nabi yang Dinubuatkan oleh Musa dalam Ulangan - Pranoz Theozen Pati; Kristanto Kristanto (KINAA: Jurnal Teologi, 2021)
The prophet is an important figure in the Bible who was sent by God to give advice and teaching to mankind in the prophet's time, until now for believers. So it is important to know the prophets written in the Bible. The prophecy of the prophet Moses of the coming of a prophet who was promised to the Israelites gave rise to different views among Christians and Islamic leaders about who the prophet who would come was. Islamic figures claim that the prophet is Muhammad, and Christians claim that prophet is Jesus Christ. Based on the analysis of qualitative research methods with a literature review approach, based on the criteria, namely, coming from the midst and from among the Israelites, like Moses, God will put His Word into the mouth of the prophet. Then it was revealed that the prophet foretold by Moses in Deuteronomy 18:15-19 was Jesus Christ.